Treatment of Heavy Metals in Groundwater by The Carbonization of Lemon Peels and Coconut Shells - Khairul Anuar, Ameeroul Aizzuwan; Ts. Dr. Mohd Ariff bin Ahmad Nazri (Recent Trends in Civil Engineering and Built Environment, 2022)
Groundwater can be one of the sources for the fresh water that can be utilized for various purposes. However, the rapid growth of industrial and agricultural activities leads to the pollution of the surface water and also the groundwater quality. The presence of heavy metals (iron and copper) caused by the anthropogenic activities does affect the quality of the groundwater. This study is focusing on the properties of groundwater in Universiti Tun Hussein Onn Malaysia (UTHM) and the method that can remove or reduce the concentration of heavy metals such as iron and copper in the groundwater. Activated carbon from coconut shells and lemon peels as the natural adsorbents were studied and the efficiency of both materials were compared. The scope of this study was based primarily on a comprehensive literature review to gather comprehensive information on the activated carbon used, as well as expectations for its usage on groundwater samples in RECESS UTHM. The groundwater data at RECESS UTHM was obtained from the previous research papers. The best values for each parameter from both activated carbons was selected based on the nearest values to the values from previous research journals. The average optimum dosage for coconut shells activated carbon was 0.77g were capable of removing 92.4% of heavy metal presents in the groundwater. Meanwhile, the lemon peels were 1.28g with 91.88% percentage removal. The optimum contact time for lemon peels was at 83 minutes with 81.46% percentage removal. On the other hand, the optimum contact time for coconut shells activated carbon was at 100 minutes with 89.01% percentage of removal. The finding of this study will contribute to the benefit of the society in advancement of knowledge on the properties of groundwater. The groundwater quality can be improved and can be used as a source of freshwater for domestic purposes.